What are the essential features of a successful surgical registry? a systematic review. Issue 9 (24th September 2017) - Mandavia, Rishi; Knight, Alec; Phillips, John; Mossialos, Elias; Littlejohns, Peter; Schilder, Anne
Abstract : Objective: The regulation of surgical implants is vital to patient safety, and there is an international drive to establish registries for all implants. Hearing loss is an area of unmet need, and industry is targeting this field with a growing range of surgically implanted hearing devices. Currently, there is no comprehensive UK registry capturing data on these devices; in its absence, it is difficult to monitor safety, practices and effectiveness. A solution is developing a national registry of all auditory implants. However, developing and maintaining a registry faces considerable challenges. In this systematic review, we aimed to identify the essential features of a successful surgical registry. Methods: A systematic literature review was performed adhering to Preferred Reporting Items for Systematic Review and Meta-Analysis recommendations. A comprehensive search of the Medline and Embase databases was conducted in November 2016 using the Ovid Portal. Inclusion criteria were: publications describing the design, development, critical analysis or current status of a national surgical registry. All registry names identified in the screening process were noted and searched in the grey literature. Available national registry reports were reviewed from registry websites. Data were extracted using a data extraction table developed by thematic analysis. Extracted data were synthesised into a structured narrative. Results: Sixty-nine publications were included. The fundamentals to successful registry development include: steering committee to lead and oversee the registry; clear registry objectives; planning for initial and long-term funding; strategic national collaborations among key stakeholders; dedicated registry management team; consensus meetings to agree registry dataset; established data processing systems; anticipating challenges; and implementing strategies to increase data completion. Patient involvement and awareness of legal factors should occur throughout the development process. Conclusions: This systematic review provides robust knowledge that can be used to inform the successful development of any UK surgical registry. It also provides a methodological framework for international surgical registry development.